2020
DOI: 10.1016/j.jacbts.2020.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Development of Tissue Engineered Heart Valves for Percutaneous Transcatheter Delivery in a Fetal Ovine Model

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…There have been recent advances in developing fetal TAVR, Zakko et al demonstrated the transcatheter delivery of a tissue-engineered heart valve in a fetal ovine model, which survived to birth. 37 …”
Section: Discussionmentioning
confidence: 99%
“…There have been recent advances in developing fetal TAVR, Zakko et al demonstrated the transcatheter delivery of a tissue-engineered heart valve in a fetal ovine model, which survived to birth. 37 …”
Section: Discussionmentioning
confidence: 99%
“…The risk of damage to the valve in the event of a stent complication or to the stent in the case of a valvular intervention has yet to be fully described. Still in its beginning stages, a zinc–aluminum alloy degradable metal stent housing a synthetic, electrospun polycaprolactone valve is being used in a fetal transcatheter ovine model and may provide an alternative solution to the issue of long-term stent placement [ 42 ]. Despite zinc being an essential metal for many cellular processes, there are still only limited in vitro and in vivo data demonstrating its impact within the cardiovascular system and tissue regeneration pathway [ 50 , 51 ].…”
Section: Tissue-engineered Pulmonary Valvementioning
confidence: 99%
“…The image in the top left is from an editorial on a PTFE RV-PA conduit [ 40 ]. The images in the bottom left box are of different views of the Xeltis biodegradable pulmonary valve conduit [ 41 ] from a bioabsorbable metal stent PVR from Zakko et al, 2020 [ 42 ]. PVR: Pulmonary valve replacement; PV: pulmonary valve; RV: Right ventricle; the green and red squares are to emphasize.…”
Section: Figurementioning
confidence: 99%
“…Consequentially, electrospun microfibrous substrates have been used in numerous applications for tissue engineering (Xue et al, 2019). Polycaprolactone (PCL) is commonly used for substrate fabrication in tissue engineering for its biocompatibility, flexibility, electrospinnability, and slow biodegradation rate, and it has been FDA‐approved for use in many medical applications (Zakko et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Polycaprolactone (PCL) is commonly used for substrate fabrication in tissue engineering for its biocompatibility, flexibility, electrospinnability, and slow biodegradation rate, and it has been FDA-approved for use in many medical applications (Zakko et al, 2020).…”
Section: Introductionmentioning
confidence: 99%